Efektivitas Penggunaan Modifikasi Game Pictionary Terhadap Penguasaan Goi Siswa SMA - Devani Oktafiana; Nova Yulia (Universitas Negeri Padang, 2023)
In general, there are three types of languages studied in Indonesia, namely regional languages, Indonesian and foreign languages. One of the foreign languages studied is Japanese. In learning Japanese, the lack of mastery of goi is a common obstacle for students. SMAN 1 Tilatang Kamang is one of the schools that has Japanese language lessons. Where Japanese is used as one of the cross-interest lessons. From the results of observations and interviews that have been conducted with subject teachers and students, information is obtained that the ability of class XII students at SMAN 1 Tilatang Kamang in the aspect of mastery of goi is still lacking. One of the reasons is the lack of student interest in learning goi, and the goi that has been studied before has been forgotten. Therefore, certain techniques are needed to increase student interest and make it easier for students to learn goi. The use of the Pictionary game modification is possible to overcome this. The purpose of this study was to determine the effectiveness of the Pictionary game modification on goi mastery in class XII across Japanese language interests at SMA Negeri 1 Tilatang Kamang. This research is a quantitative research type of experiment with a posttest only control group design. The data was taken from the total research sample for class XII IPA 2 and class XII IPS 3 totaling 68 people. Based on the results of the t-test, it was concluded that the alternative hypothesis (H1) was accepted at a significant level of 5% because tcount>ttable (3.46>2.00), which means that the mastery of goi in the experimental class was much different from the control class. In other words, the use of the Pictionary game modification is effective against goi mastery.